" Utilization of Mangrove Forest Resources for Human Livelihoods in Uzere, Delta State, Nigeria " (2000)
The study was carried out to assess the various ways Uzere mangrove forest is utilized by the forest edge communities. Data were obtained from 300 residents within the three communities in Uzere Kingdom using systematic random sampling. The study employed questionnaires to elicit information on the uses of the mangrove forest, the socio-economic factors that influence uses. Data obtained were analysed using simple statistics and correlation analysis. All the respondents use the forest for various livelihood activities. These include: logging (5.3%), farming (49.7%), fuel wood gathering (18.3%), fruits gathering (1.0%), hunting (6.0%), fish farming (6.3%), palm wine tapping (0.7%), seeds (0.3%) and medicinal plants (2.7%) collections. Gender and years of residence are the only socio-economic variables that significantly influenced the uses of Uzere mangrove forest. About 70% of the respondents market the products from the mangrove forest as a source of income. The mean annual earnings from mangrove resources marketing is N2,920,514.51 (US$19,470.00). The mangrove forest contributes significantly to human livelihoods in the study area. There is a need for sustainable management of the mangrove forest and valuation of forest goods as a means of preventing forest degradation and deforestation.